A Decade of Software Engineering Best Practices Adoption in Small Companies: A Quasi-Systematic Mapping - Costa, Alex; Saraiva, Juliana; Aguiar, Yuska (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2017: Anais do XIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2017.6049, 2017)
SWEBOK is a guideline that provides information about Software Engineering (SE) knowledge, including a list of Best Practices (BPs) for adopting. However, small companies have restrictions such as, limited budget, reduced schedule, and, small staff that can hinder the advantages of these BPs adoption. Thus, this paper investigated the last decade of BPs adoption reported by small companies’ environment. A quasi-systematic mapping was conducted for assessing studies that addressed this issue, and it was possible to observe that the most prominent BPs adopted are “test application” and “software process model adoption”. On the other hand, “limited budget” and “staff size” were found as causes for non-adoption of SWEBOK’s BPs.